Cinema and Social Change in Germany and Austria (Book collections on Project MUSE., 2011)
Making the greatest artistic impact since the 1970s, contemporary cinema is responding to questions of globalisation and the effects of societal and economic change on the individual. This book explores this trend by investigating different thematic and aesthetic strategies and alternative methods of film production and distribution.